Clinical benefits and safety of renal denervation in severe arterial hypertension: A long‐term follow‐up study. Issue 10 (3rd September 2020) - Naduvathumuriyil, Tino; Held, Ulrike; Steigmiller, Klaus; Denegri, Andrea; Cantatore, Silviya; Obeid, Slayman; Flammer, Andreas J.; Ruschitzka, Frank; Lüscher, Thomas F.; Sudano, Isabella
Abstract: The clinical benefits of renal denervation are still under discussion, since randomized controlled clinical studies have provided inconsistent results. The present retrospective study examined the clinical effects of renal denervation with focus on office blood pressure, heart rate, and changes in renal function. Patients with treatment‐resistant hypertension (blood pressure ≥ 140/90 mm Hg in spite of 3 antihypertensive drugs including a diuretic) underwent renal denervation at the University Hospital of Zurich, Switzerland and were followed up until 36 months. Renal denervation was performed using 3 different renal denervation systems. The primary outcome consisted of change in office blood pressure, heart rate, and plasma creatinine at 1, 6, 12, 24, and 36 months after renal denervation. 58 patients underwent renal denervation between August 2010 and December 2017. After exclusion, 50 patients were included in the analyses. At 36 months, the mean office systolic and diastolic blood pressure change was −26.4/‐8.8 mm Hg (95% CI: −34.6 to −18.2/‐13.5 to −4.2 mm Hg; P  < .001 for both). Office heart rate showed no significant change during follow‐up ( P  = .361). Plasma creatinine increased from 90.6 µmol/L (95% CI: 82.1 to 99.0 µmol/L) at baseline to 102.1 µmol/L (95% CI: 95.8 to 108.3 µmol/L) at 36 months ( P  = .007). No major adverse events occurred. Renal denervation is a safe and effective procedure for patients with treatment‐resistant hypertension with a clinically significant antihypertensive effect. Further randomized trials are needed to determine the specific context within which renal denervation should be considered a therapeutic option in antihypertensive care.